CD4+ T cells regulate sickness-induced anorexia and fat wasting during a chronic parasitic infection - Samuel E. Redford; Siva Karthik Varanasi; Karina K. Sanchez; Natalia R. Thorup; Janelle S. Ayres (Cell Reports, 2023)
Summary: Infections cause catabolism of fat and muscle stores. Traditionally, studies have focused on understanding how the innate immune system contributes to energy stores wasting, while the role of the adaptive immune system remains elusive. In the present study, we examine the role of the adaptive immune response in adipose tissue wasting and cachexia using a murine model of the chronic parasitic infection Trypanosoma brucei, the causative agent of sleeping sickness. We find that the wasting response occurs in two phases, with the first stage involving fat wasting caused by CD4+ T cell-induced anorexia and a second anorexia-independent cachectic stage that is dependent on CD8+ T cells. Fat wasting has no impact on host antibody-mediated resistance defenses or survival, while later-stage muscle wasting contributes to disease-tolerance defenses. Our work reveals a decoupling of adaptive immune-mediated resistance from the catabolic response during infection.